Morphological and clinical study of lateral malleolus fractures based on fracture mapping: a retrospective study - Ruizhi Cai; Shuo Feng; Chuhan Chen; Hao Lu; Hailin Xu (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background The traditional classification for lateral malleolus fracture has its limitations. In this study, we introduced a three-dimensional (3D) fracture mapping technique using computed tomography (CT) data to assess fracture line distributions and their impact on patient outcomes, offering a refined classification approach. Methods Retrospectively, we analysed 97 patients who underwent lateral malleolus fracture surgeries (2014–2019), using CT Digital Imaging and Communications in Medicine data to create 3D models and fracture maps. This methodology refined the Danis–Weber classification and enabled the assessment of fracture severity and syndesmotic stability through clinical scoring. Results Danis–Weber type B fractures were predominant (83.5%), showing a distinct pattern. Subtypes were identified based on the bone fragments that are clinically associated with increased injury severity but did not significantly affect syndesmotic stability or prognostic scores. Conclusion The 3D fracture map provides a detailed view of fracture characteristics, enabling precise classification. In type B fractures, bone fragments indicating higher trauma do not predict clinical outcomes, thereby supporting personalised surgical planning.